2003
DOI: 10.1016/s0925-4773(03)00020-0
|View full text |Cite
|
Sign up to set email alerts
|

Tob proteins enhance inhibitory Smad-receptor interactions to repress BMP signaling

Abstract: Tob inhibits bone morphogenetic protein (BMP) signaling by interacting with receptor-regulated Smads in osteoblasts. Here we provide evidence that Tob also interacts with the inhibitory Smads 6 and 7. A yeast two-hybrid screen identified Smad6 as a protein interacting with Tob. Tob co-localizes with Smad6 at the plasma membrane and enhances the interaction between Smad6 and activated BMP type I receptors. Furthermore, we have isolated Xenopus Tob2, and show that it cooperates with Smad6 in inducing secondary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…In an effort to understand the regulation of Orb2 prion-like conversion, White-Grindley et al (2014) noticed that Orb2A protein has a very short half-life ( 1 h) consistent with its low abundance. Transducer of Erb2 or Tob, a previously known regulator of SMAD (small body size and mothers against decapentaplegic)-dependent transcription (Yoshida et al 2000(Yoshida et al , 2003 and CPEB-mediated translation (Hosoda et al 2011) associates with both Orb2A and Orb2B, but increases the half-life of only Orb2A. Both Orb2 and Tob are phosphoproteins and PP2A controls the phosphorylation status of Orb2A and Orb2B.…”
Section: Role Of Prion-like State Of Drosophila Orb2 In the Persistenmentioning
confidence: 99%
“…In an effort to understand the regulation of Orb2 prion-like conversion, White-Grindley et al (2014) noticed that Orb2A protein has a very short half-life ( 1 h) consistent with its low abundance. Transducer of Erb2 or Tob, a previously known regulator of SMAD (small body size and mothers against decapentaplegic)-dependent transcription (Yoshida et al 2000(Yoshida et al , 2003 and CPEB-mediated translation (Hosoda et al 2011) associates with both Orb2A and Orb2B, but increases the half-life of only Orb2A. Both Orb2 and Tob are phosphoproteins and PP2A controls the phosphorylation status of Orb2A and Orb2B.…”
Section: Role Of Prion-like State Of Drosophila Orb2 In the Persistenmentioning
confidence: 99%
“…The binding of TOB/BTG family proteins to Caf1/Pop2 inhibits the initiation of transcription by the CCR4/Not complex. [11][12][13] TOB can interact simultaneously with PABPC1 and CCR4-CAF1 to regulate mRNA turnover through deadenylation. [14][15][16] In addition, TOB/ BTG family proteins have been shown to associate with homeobox transcription factors such as Hoxb9.…”
Section: Uiccmentioning
confidence: 99%
“…17 Finally, TOB is able to negatively regulate Smad-mediated transcription. TOB enhances Smad binding to DNA, activating a transcriptional repressor complex [11][12][13] that modulates TGF-b/BMP signaling. 18 The role of TOB proteins in cancer became apparent when it was observed that mice lacking TOB spontaneously develop tumors, primarily in lung, liver and lymph nodes.…”
Section: Uiccmentioning
confidence: 99%
“…This cyclin functions as a regulatory subunit of CDK2 and plays a role in cell cycle G1/S transition (Gudas et al, 1999). Tob 1 is an antiproliferative protein and it is known for inhibiting bone morphogenetic protein (BMP) signaling (Yoshida et al, 2003). These two genes were found to be upregulated in normal human fibroblasts exposed to low dose of UVC (Gentile et al, 2003).…”
Section: Hierarchical Clustering and Common Uvc-regulated Genesmentioning
confidence: 99%